Mitigasi Resiko Halal pada Layanan Online Food Delivery - Ellisa Br Pardede; Harwati Harwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to identify halal contamination risks in online food delivery (OFD) services and develop effective mitigation strategies. The research employs the House of Risk (HOR) method consisting of two phases: identifying and prioritizing risk agents and determining mitigation actions. Data were collected through interviews, observations, and questionnaires involving 100 delivery drivers in Yogyakarta. The results indicate that the main risks arise from the absence of delivery bag partitions, improper driver behavior in mixing orders, and order overload. The highest Aggregate Risk Priority (ARP) value is associated with delivery bag design issues. Priority mitigation strategies include modifying delivery bags with partitions, grouping orders, and limiting the number of deliveries per trip. The Wilcoxon test results show a significant difference before and after implementing mitigation strategies. This study contributes to improving safety, hygiene, and halal assurance in OFD services.